Effectiveness and safety of hydrogen inhalation therapy as an additional treatment for hypertension in real-world practice: a retrospective, observational study in China - Ji, Hongxiang; Sun, Hualin; Zhang, Yinghui; Zhao, Ziyi; Gao, Xin; Wang, Chunhe; Yang, Yang; Zhang, Xiaodong; Gao, Jianyong; Man, Dequan; Yang, Qian; Yang, Ying; et al. (Frontiers in Cardiovascular Medicine, 2024)
AimTo evaluate the real-life effectiveness and safety of hydrogen inhalation (HI) therapy as an additional treatment in Chinese adults with hypertension.MethodsThis observational, retrospective clinical study included hypertensive patients receiving routine antihypertensives with or without HI initiation from 2018 to 2023. Participants were assigned to the HI group or non-HI group (control group) after propensity score matching. The changes in mean systolic blood pressure (SBP) level during the 24-week follow-up period in different groups were examined primarily. The secondary outcome was the changes in diastolic blood pressure (DBP) and blood pressure (BP) control rate during the study. Several subgroup and sensitivity analyses were performed to confirm the robustness of our main findings. Adverse event (AE) was also assessed in patients of both groups.ResultsIn total, we selected 2,364 patients into the analysis. Both mean SBP and DBP levels significantly decreased in the HI group compared to control group at each follow-up visit with the between group difference of −4.63 mm Hg (95% CI, −6.51 to −2.74) at week 8, −6.69 mm Hg (95% CI, −8.54 to −4.85) at week 16, −7.81 mm Hg (95% CI, −9.57 to −6.04) at week 24 for SBP, and −1.83 mm Hg (95% CI, −3.21 to −0.45) at week 8, −2.57 mm Hg (95% CI, −3.97 to −1.17) at week 16, −2.89 mm Hg (95% CI, −4.24 to −1.54) at week 24 for DBP. Patients in the HI group were more likely to attain controlled BP at the follow-up period with odds ratio of 1.44 (95% CI, 1.21–1.72) at week 8, 1.90 (95% CI, 1.59–2.27) at week 16, and 2.24 (95% CI, 1.87–2.68) at the end. The trends of subgroup and sensitivity analyses were mostly consistent with the main analysis. The incidences of AEs were similar between the HI group and control group with all p-value >0.05.ConclusionThe HI therapy is related to significant amelioration in BP levels with acceptable safety profile in Chinese hypertensive adults after 24 weeks of treatment, building a clinical ground for further research to evaluate the antihypertensive effect of HI therapy.